Antibody dynamics in dogs submitted to different canine visceral leishmaniasis treatment protocols - Eliesse Pereira Costa; Gisele Vaz Aguirre Samoel; Gilneia da Rosa; Vanessa Osmari; Michelli Lopes de Souza; Luís Felipe Dias Lopes; Fernanda Silveira Flôres Vogel; Sônia de Avila Botton; Luís Antônio Sangioni (Revista Brasileira de Parasitologia Veterinária)
Abstract This study evaluated dynamics of antibodies in dogs treated for canine visceral leishmaniasis (CVL). Twenty-one dogs naturally infected by Leishmania spp. were grouped based on the treatment protocol: G1 (n=4) received allopurinol; G2 (n=10) allopurinol with miltefosine; and G3 (n=7) allopurinol, miltefosine and Leish-Tec® vaccine. The dogs were monitored monthly for a period of one year. To verify serum antibody titers, an indirect immunofluorescence reaction was performed. We found that dogs from G1 and G2 had lower clinical scores and antibody titers, when compared to the parameters evaluated in pre-treatment; however, clinical relapses were observed in three animals. In G3, clinical scores were lower than pre-treatment; however, they presented relatively stable antibody titers and no clinical relapse was observed. All animals submitted to the evaluated treatment protocols showed relative improvement in clinical signs. Furthermore, the immune response of animals must be considered, given the challenges of parasitic loads in infections. Therefore, it is necessary to complement the methods of clinical and therapeutic monitoring of dogs with CVL in order to establish the risk of transmissibility of the agent in infected and treated dogs.